Adsorption of Escherichia coli in Different Soils - Ling, T. Y.; Goh, S. H.; Kasing, A. (Universiti Malaysia Sarawak, 2013)
Adsorption of E.coli on soils determines its availability for movement during runoff events. In this study, adsorption of E.coli is determined in two different soils, a silt loam and a clay loam. Clay loam was found to adsorb significantly more E.coli than silt loam. Clay loam absorbed 81.5% and 86.2% of E.coli at low and high initial concentrations respectively whereas silt loam was found to adsorb 39.4% and 75% at low and high initial concentrations respectively. Results show that adsorption isotherm could be represented by linear adsorption isotherm. Distribution coefficient was found to be 0.65 and 3.13 ml/g for silt loam and 4.40 and 6.29 ,l/g for clay loam. The distribution coefficient is dependent on the initial concentration of E.coli.